2009
DOI: 10.1073/pnas.0903710106
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing rotary processes in synthetic molecular motors

Abstract: We deal with the issue of quantifying and optimizing the rotation dynamics of synthetic molecular motors. For this purpose, the continuous four-stage rotation behavior of a typical light-activated molecular motor was measured in detail. All reaction constants were determined empirically. Next, we developed a Markov model that describes the full motor dynamics mathematically. We derived expressions for a set of characteristic quantities, i.e., the average rate of quarter rotations or ''velocity,'' V, the spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 52 publications
5
74
0
Order By: Relevance
“…Several other studies have argued that to maintain a high flux, large free energy increases should be broken up into smaller pieces, with no individual free energy change too large [11][12][13]. Even in synthetic molecular motors, it is thought that similar forward rates are optimal (to avoid 'traffic jams') [15]. We find an unequal optimal dissipation allocation occurs when: the nonequilibrium steady-state flux is maximized ; optimization is subject to fixed total dissipation budget per cycle ; the ratio of forward and reverse rate constants varies exponentially, not linearly, with dissipation (Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have argued that to maintain a high flux, large free energy increases should be broken up into smaller pieces, with no individual free energy change too large [11][12][13]. Even in synthetic molecular motors, it is thought that similar forward rates are optimal (to avoid 'traffic jams') [15]. We find an unequal optimal dissipation allocation occurs when: the nonequilibrium steady-state flux is maximized ; optimization is subject to fixed total dissipation budget per cycle ; the ratio of forward and reverse rate constants varies exponentially, not linearly, with dissipation (Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies have found that under a variety of criteria, an even allocation of dissipation across all transitions in a machine cycle is optimal [6][7][8][9][10][11][12][13][14][15]. However, many models parametrized to experimental biomolecular machine dynamics contain effectively irreversible transitions [16][17][18][19][20][21][22], suggesting that some transitions dissipate a large amount of free energy compared to the 'reversible' transitions in the same cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanism is therefore in concert with the well-studied unidirectional rotation of the Feringa motor, which we use. [11][12][13][14] For the azimuthal orientation of the molecules on the surface a preference of the 'wheel-wheel axle' at multiples of 60° relative to the Cu(111) surface is found (Fig. 5a), reflecting arrangement with the underlying crystal directions.…”
Section: Resultsmentioning
confidence: 99%
“…8 Several synthetic molecular motors have been synthesized, 2,9,10 including a molecular motor developed by Feringa and co-workers that rotates at a frequency in the MHz regime. [11][12][13][14] For ultimate control of molecular machines it is essential that the motor exhibits only one sense of rotation, resulting in unidirectional translation of the molecular machine on a surface, thus only forward and no backward motion, in contrast to random motion in all directions. 2 For synthetic molecular machines to contribute to the vision of nanotechnology by transporting molecular species and cargo on surfaces, the motion of…”
Section: Introductionmentioning
confidence: 99%
“…Actually, in many cases, such basic quantities are the only ones that can be measured directly in experiments. Recent discussion about a modified one-dimensional hopping model indicates that the method in the paper is good in more general hopping models, in which the particle in state i has more than two choices (states i − 1 and i + 1) to jump out of its present state [27]. …”
Section: Discussionmentioning
confidence: 97%